A Model Kepemimpinan Transformasional Kepala Sekolah dalam Meningkatkan Mutu Manajemen Sekolah - Annisa Dwi Asmarani; Siti Harfihamzah Indra Naomi; Yessy Ardina Emilia; Muflihatun; Nina Oktarina; Fathur Rokhman; Gunawan Tjokro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The transformation of 21st-century education requires schools to adapt through effective organizational management, with principal leadership serving as a key factor in improving school management quality. This study aims to analyze the role of transformational leadership in enhancing school management and to formulate a contextual and effective leadership model for educational management. The research employs a qualitative approach using a systematic literature review of scientific publications related to transformational leadership and educational management. The findings indicate that transformational leadership significantly contributes to school management quality through four main dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. This leadership approach enhances teachers’ motivation, commitment, and performance, fosters a collaborative school culture, and optimizes management functions including planning, organizing, implementation, and supervision. The study confirms that transformational leadership is a strategic model supporting sustainable improvement in school management and provides both theoretical and practical contributions to educational leadership practices.